No Underlying Cause: A Case of a Fatal Neuroendocrine Lung Tumor - Dennison, Alexandria; Ali, Nafisha; Ibrahim, Ahmed (Global Journal of Medical and Clinical Case Reports, 2019)
A 34 year old female with metastasizing neuroendocrine lung carcinoma with no underlying etiologies. Patient was diagnosed with stage 4 lung neuroendocrine cancer with treatment options limited due to intellectual disability and overall poor prognosis. The patient had a rapid decline over a 5 week period with decreased intake, decreased appetite, and overall azotemia and resulted in patient’s death.